PENGARUH SELF ACTION DAN SELF EFFICACY TERHADAP KREATIVITAS MAHASISWA DALAM KEGIATAN PRAKTIKUM BIOLOGI UMUM JURUSAN PENDIDIKAN BIOLOGI FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Tauhid, Muh; Safei, Safei; Hidayat, Muhammad Yusuf (Jurnal Biotek, 2016)
This research is aimed to find out description self action, selfefficacy, and of students’ creativity also to effect of self actionand self efficacy towards the students’ creativity in general biology practical lab. The population of this research was the all students of Biology Education Department, UIN Alauddin Makassar starting from 2012 generation until 2015 generation that consist 11 classes with amount of 400 students. While the sample have taken by used of Simple Random Samplingtechnique,sothatthis research obtained74 students. The Instrument was used questioner. Data analysis technique was used descriptive statistic and inferential technique. The results of this research through descriptive analysis obtained mean score for self action was 70,20 in the medium category, mean score of self efficacy was 45,28 in the medium category, and mean score of students’ creativity was 51,93 in the medium category. Inferential statistic analysis results with F tes obtained that score Fcount>Ftable (13,778>3,13). Thus, it can be concluded that there is significant effect between self action and self efficacy towards students’ creativity in general biology practical lab at Biology Education Department of UIN Alauddin Makassar.